Castor oil based polyurethane adhesive content on OSSB produced with soybean straw - Silva, João Vitor Felippe [UNESP]; Silva, Maria Fernanda Felippe [UNESP]; Ferreira, Bruno Santos [UNESP]; Fiorelli, Juliano; Christoforo, André Luis; Campos, Cristiane Inácio De [UNESP] (Associação Nacional de Tecnologia do Ambiente Construído - ANTAC, 2020)
Oriented Structural Straw Board (OSSB) panels are composites made from straw originally from agricultural residues and non-formaldehyde based adhesive, whose main application is for construction as a closing and ceiling material. The objective of this study was to evaluate the effect of the polyurethane adhesive content on physical and mechanical properties of OSSB produced with locally available SbS (soybean straw). Four castor oil based polyurethane ratios (6%, 9%, 12% and 15%, by mass of the SbS) were tested. OSSB was evaluated according to European standards for wood-based composites; also, a physical and chemical characterization of the SbS was performed. SbS has an irregular shape, which reduced the OSSB mechanical performance due to the low densification of the composite and the development of transversal cracks on the SbS after the OSSB manufacturing process. The static bending and thickness swelling performance of SbS OSSB was not improved by the increase of polyurethane adhesive content. SbS low ash content and neutral pH extractives indicates that probably its chemical properties should not affect the setting of the adhesive.

Painéis OSSB (Oriented Structural Straw Board) são compósitos produzidos com palha proveniente de resíduos agrícolas e utilizando de adesivo sem formaldeído, cuja principal aplicação se volta para a construção civil como material de fechamento e forros. Este trabalho teve como objetivo avaliar o efeito do teor de poliuretano no adesivo sobre propriedades físicas e mecânicas do OSSB produzido com SbS (palha de soja) localmente disponível. Quatro composições de poliuretano à base de óleo de mamona (6%, 9%, 12% e 15%, em relação à massa de palha) foram testadas. Painéis OSSB foram avaliados de acordo com os padrões europeus para compósitos à base de madeira; também, uma caracterização física e química da SbS foi realizada. A SbS possui formato irregular, o que reduziu o desempenho mecânico do OSSB devido à baixa densificação do compósito e ao desenvolvimento de trincas transversais na SbS após o processo de fabricação do compósito. O desempenho em testes de flexão estática e inchamento de espessura do OSSB não foi melhorado pelo aumento do teor de adesivo de poliuretano. A SbS apresentou baixo teor de cinzas (menos que 4.3%) e pH neutro, isto indica que estas propriedades químicas provavelmente não afetaram na cura do adesivo.
Efeito do teor de adesivo poliuretano à base de óleo de mamona em painéis OSSB de palha de soja
Keywords: Glycine max L; Agricultural residue; Structural composite; Glycine max L; Resíduo agrícola; Compósito estrutural